2011
DOI: 10.1002/chem.201003166
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of cyclo‐Mumbaistatin Analogues through Anionic Homo‐Fries Rearrangement

Abstract: The structurally unique polyketide mumbaistatin is the strongest naturally occurring inhibitor of glucose-6-phosphate translocase-1 (G6P-T1), which is a promising target for drugs against type-2 diabetes mellitus and angiogenic processes associated with brain tumor development. Despite its high relevance, mumbaistatin has so far withstood all attempts towards its total synthesis. In the present study an efficient total synthesis of a deoxy-mumbaistatin analogue containing the complete carbon skeleton and a spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 128 publications
1
12
0
Order By: Relevance
“…Schmalz et al [202] recently reported a tandem anionic homo-Fries rearrangement/ lactonization [203] for the synthesis of cyclo-mumbaistatin analogue 436 (Scheme 105).…”
Section: Anionic Homo-fries Rearrangement/lactonizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Schmalz et al [202] recently reported a tandem anionic homo-Fries rearrangement/ lactonization [203] for the synthesis of cyclo-mumbaistatin analogue 436 (Scheme 105).…”
Section: Anionic Homo-fries Rearrangement/lactonizationmentioning
confidence: 98%
“…Thus, the reaction sequence was optimized to maximize the yield of 439, proposed to arise from dehydration of the intermediate hemiacetal 441, followed by Ferrier rearrangement (Scheme 107). By inclusion of Scheme 105 Anionic homo-Fries rearrangement in the synthesis of a spiroacetal [202] Scheme 106 Unexpected Ferrier rearrangement in the synthesis of the southern hemisphere of spirastrellolide B [28] Scheme 107 Optimization of the Ferrier rearrangement in the synthesis of the southern hemisphere of spirastrellolide B [28] PTSA in the reaction sequence, the yield of the unsaturated spiroacetal 443 could be improved from 24 % to 62 %.…”
Section: Ferrier Rearrangementmentioning
confidence: 98%
“…Stirring compound 1 with acetic anhydride in ethyl acetate in the presence of triethylamine for 4.5 h at 5–10°C gave 1,4‐dioxo‐1,4‐dihydronaphthalen‐2‐yl acetate ( 307 ) in yield 80% . Refluxing compound 1 with SO 2 Cl, oxyalyldichloride in DMF , Br 2 or any bromating agent in AcOH afforded 2‐halonaphthalen‐1,4‐dione 308 . Also, heating 1 with 1‐bromo‐3‐methylbut‐2‐ene in DMSO in the presence of sodium hydride (NaH) at 45°C for 2 h produced 2‐((3‐methylbut‐2‐en‐1‐yl)oxy)naphthalen‐1,4‐dione ( 309 ) .…”
Section: Reactivity Of Lawsonementioning
confidence: 99%
“…16,17 Fries rearrangement has been extensively used in the synthesis of organic pharmaceuticals and gradually become a research hotspot in recent years. [18][19][20][21][22] In the synthesis of DPC, organotin, organotitanium and other Lewis acids are usually used as catalysts, and the pilot-scale amplication reaction is carried out under high temperature and high pressure.…”
Section: Introductionmentioning
confidence: 99%